2011
DOI: 10.1073/pnas.1016863108
|View full text |Cite
|
Sign up to set email alerts
|

Sortase-catalyzed transformations that improve the properties of cytokines

Abstract: Recombinant protein therapeutics often suffer from short circulating half-life and poor stability, necessitating multiple injections and resulting in limited shelf-life. Conjugation to polyethylene glycol chains (PEG) extends the circulatory half-life of many proteins, but the methods for attachment often lack specificity, resulting in loss of biological activity. Using four-helix bundle cytokines as an example, we present a general platform that uses sortasemediated transpeptidation to facilitate site-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
153
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(155 citation statements)
references
References 30 publications
2
153
0
Order By: Relevance
“…Orthogonal SrtA variants have previously been used in the dual N-and C-terminal functionalization of target proteins (12,24). However, in these applications, the low activity and poor orthogonality of the enzymes greatly limited the scope of available reactions (24). To test whether the combined use of reprogrammed sortases can overcome these limitations, we attempted to synthesize dual N-and C-terminally functionalized proteins of biomedical interest.…”
Section: Reprogrammed Sortases Enable the Facile Synthesis Of Complexmentioning
confidence: 99%
“…Orthogonal SrtA variants have previously been used in the dual N-and C-terminal functionalization of target proteins (12,24). However, in these applications, the low activity and poor orthogonality of the enzymes greatly limited the scope of available reactions (24). To test whether the combined use of reprogrammed sortases can overcome these limitations, we attempted to synthesize dual N-and C-terminally functionalized proteins of biomedical interest.…”
Section: Reprogrammed Sortases Enable the Facile Synthesis Of Complexmentioning
confidence: 99%
“…structure of hGH in complex with the extracellular domain of its receptor indicate that the key residues involved in binding the receptor reside in helices 1, 3, and 4, with the N and C termini of hGH distal to the binding interface (19,20). Moreover, previous studies have shown that covalent cross-linking of the N and C termini of four-helix-bundle cytokines with a PEGylated short peptide sequence does not significantly affect the biological activities of the cytokines (21). Therefore, we reasoned that connecting the two termini of hGH with the CDR3H stalk of the bovine antibody BLV1H12 would likely yield a fusion protein with wild-type hGH activity but with the superior pharmacological properties of the Ig scaffold.…”
Section: Resultsmentioning
confidence: 98%
“…To improve its pharmacokinetics, IFN-α is usually conjugated with 40 kDa branched PEG (PEGASYS) or 20 kDa linear PEG (PEGINTRON), but its activity is significantly reduced to 7% for PEGASYS [7] or 28% for PEGINTRON [8]. It is anticipated that the activity of protein-polymer conjugate can be well remained by site-specific conjugation at the sites that are distant from the protein's receptor interaction site, such as the C terminus of IFN-α [9][10][11].…”
mentioning
confidence: 99%